Plan de negocios para la creación de una empresa productora y exportadora de pastel de cangrejo con malanga congelado y empacado al vacío a Miami, Estados Unidos. - Sánchez Urbina, Emily Sofía (2020)
The current business plan purpose is to prove the viability for the creation of a start- up company that produces and exports crab-pie with frozen and vacuumpacked taro to Miami, United States. It presents an avant-garde food option in flavors with a combination of ingredients, traditional and contemporary cooking techniques. The analysis is based on the internal and external market factors determined favorable results on the environment. The customer's analysis reflects the acceptance of this new and innovative product in its environment. The non-conventional ingredients catch the customers attention when they are blended, but they claim that the challenge is to try new things. The value proposition of “Crab Delight” company is to offer a precooked product, ready to be baked in a few minutes, and to give the possibility of enjoying a delicious and unique salt-cake made with top quality raw materials, thanks to the strategic alliances established between the different associations of artisan crabs and local taro producers. The production will not be affected by the closure of the crab, since harvest cycles will be implemented. Regarding the marketing plan, internationalization strategies and positioning of the brand in the international market have been established through the benefits offered by the product, place of distribution and promotion. Distribution will be direct, using a strategic alliance with Elafood, the multinational company that will oversee the distribution to the main Miami supermarkets. To conclude, the initial investment required to finance the project is $ 446,697.14, distributed over 51percent in equity and the remaining 49 percent in debt, financed over 60 months with an annual interest rate of 9.33 percent. The analysis of the financial ratios reflects economic viability for both the project and the investor, with positive values and higher than the discount rates provided, respectively.